Google Classroom: Defining its Role as Learning Management System (British Journal of Multidisciplinary and Advanced Studies, 2023)
Google Classroom (GC) is a platform used by schools to continue their delivery of instructional processes during the pandemic. This study identified the extent of students' and teachers' utilization of GC's features, their assessment as a learning management system, and their experiences using the platform. Concurrent-nested mixed method was employed. Purposive criterion and random sampling were used for the selection of the participants. Findings revealed significant difference in communication and task management in the features of GC. Ease of access, perceived usefulness, communication and interaction, and perceived instruction delivery demonstrated significant difference. This implies the beneficial use of GC for participants in achieving better results in their heutagogical practices in learning and teaching. Two themes emerged from their experiences of GC. Digital interdependence specifically classifies their experiences as adeptness and ease, effectiveness and efficiency, and engagement, while discomfort, lack of resources, connectivity, and academic honesty are their experiences of technological vulnerability.